Implementation of E-leaning in Indonesian Language Subject - Widia Nopita Sari; Kasmantoni Kasmantoni; Hengki Satrisno (Jadila: Journal of Development and Innovation in Language and Literature Education, 2022)
The purpose of this study was to determine the implementation of e-learning in Indonesian class XI IBB subjects at SMAN 04 Bengkulu City. This study used qualitative research methods. Data collection techniques using observation, interviews and documentation. Data analysis techniques are data reduction, data presentation and drawing conclusions and verification. The informants in this study were the Indonesian language teacher and three students of class XI IBB. The implementation of this research began on May 06 to May 31, 2021. The results of this study were the implementation of E-learning in Indonesian Class XI IBB subjects at SMAN 04 Bengkulu City was very good and complete. Starting from the homepage, absences, announcements, messages, teaching schedules, related links, assignments, materials, my comments, achievement of basic competencies, group assignments, teacher filters, student filters and logout or exit. The implementation of e-learning makes it very easy for teachers to continue teaching and also greatly facilitates students in learning. While the obstacles to implementing e-learning in Indonesian class XI IBB subjects at SMAN 04 Bengkulu City are infrastructure, cellphones, quotas, difficult signals, servers that sometimes have errors and lack of notifications.